Fifty years of the Brazilian Academy of Neurology - Marleide da Mota Gomes (Arquivos de Neuro-Psiquiatria, 2012)
The 50th anniversary of the Brazilian Academy Neurology (BAN) is being celebrated. BAN was founded on May 5th, in 1962. The BAN initial leaders and members are treated with reverence, as well as the honorable place where its foundation took place: the Institute of Neurology, first in Brazil, at the backyards of the ancient National Hospice for the Insane, which is an important and fruitful birthplace of the Brazilian Neurology.